2016
DOI: 10.1177/2048872616679791
|View full text |Cite
|
Sign up to set email alerts
|

A consensus statement on lipid management after acute coronary syndrome

Abstract: In patients admitted for acute coronary syndrome (ACS), the guidelines of the European Society of Cardiology give a Class I, Level A recommendation for the prescription of high-intensity statins to be initiated as early as possible, regardless of the low-density lipoprotein cholesterol (LDL-C) level. Although statins are widely prescribed after ACS, the intensity of therapy and the proportion of patients achieving target LDL-C values are often not in line with recommendations due to a lack of compliance with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 66 publications
0
13
0
5
Order By: Relevance
“…A decision-making algorithm for optimizing lipidlowering therapy in the context of secondary prevention after MI has recently been published, and considers that all patients after MI are at high risk as long as treatment has not reached the maximum tolerated dose, and it also allows for the possibility of adding ezetimibe if the LDL-C value remains above the target of 70 mg/dl. 89 The place of PCSK9 inhibitors in the treatment armamentarium needs to be discussed, given the cost of this treatment. The American College of Cardiology (ACC) 90 and the European Society of Cardiology/ European Atherosclerosis Society (ESC/EAS) 91 have recently published consensus statements for the use of these new agents.…”
Section: Muscle Intolerance Should Be Verified By Ensuringmentioning
confidence: 99%
“…A decision-making algorithm for optimizing lipidlowering therapy in the context of secondary prevention after MI has recently been published, and considers that all patients after MI are at high risk as long as treatment has not reached the maximum tolerated dose, and it also allows for the possibility of adding ezetimibe if the LDL-C value remains above the target of 70 mg/dl. 89 The place of PCSK9 inhibitors in the treatment armamentarium needs to be discussed, given the cost of this treatment. The American College of Cardiology (ACC) 90 and the European Society of Cardiology/ European Atherosclerosis Society (ESC/EAS) 91 have recently published consensus statements for the use of these new agents.…”
Section: Muscle Intolerance Should Be Verified By Ensuringmentioning
confidence: 99%
“… 1 The 2013 Chinese expert consensus also emphasized that regardless of the baseline cholesterol levels, all patients with ACS events should immediately initiate and maintain intensive statin therapy long-term after discharge. 2 , 3 Based on the results of large-scale clinical trials, early intensive statin therapy has been recommended for patients with recent ACS events. Both epidemiological and interventional clinical trials have shown a strong association between elevated LDL-C level and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In Korea, the other phenotype of dyslipidemia showing high triglyceride or/and low high density lipoprotein cholesterol (HDL-C) levels is commonly found and is usually combined with abdominal obesity and elevated blood pressure and fasting glucose levels as co-morbidities for metabolic syndrome (MS). The prevalence of MS among Korean adult population is reported as high as 23.7%…”
Section: Introductionmentioning
confidence: 99%